Hypoxia mitigation by manganese-doped carbon dots for synergistic photodynamic therapy of oral squamous cell carcinoma - Zhang, Zhe; Xu, Yongzhi; Zhu, Tingting; Sang, Zhiqin; Guo, Xiaoli; Sun, Yu; Hao, Yuanping; Wang, Wanchun (Frontiers in Bioengineering and Biotechnology, 2023)
Photodynamic therapy (PDT) is widely used for cancer treatment due to its non-invasive and precise effectiveness, however, hypoxia in the tumor microenvironment greatly limits the efficacy of photodynamic therapy. Compared with conventional photosensitizers, carbon dots (CDs) have great potential. Therefore, developing a water-soluble, low-toxicity photosensitizer based on CDs is particularly important, especially one that can enhance the photodynamic efficacy using the tumor microenvironment to produce oxygen. Herein, manganese-doped carbon dot (Mn-CDs, ~ 2.7 nm) nanoenzymes with excellent biocompatibility were prepared by a solvothermal method using ethylenediaminetetraacetic acid manganese disodium salt hydrate and o-phenylenediamine as precursors. The obtained Mn-CDs have excellent near-infrared emission properties, stability, and efficient 1O2 generation. Notably, the manganese doping renders CDs with catalase (CAT)-like activity, which leads to the decomposition of acidic H2O2 in situ to generate O2, enhancing the PDT efficacy against OSCC-9 cells under 635 nm (300 mW·cm-2) irradiation. Thus, this work provides a simple and feasible method for the development of water-soluble photosensitizers with oxygen production, presenting good biosafety for PDT in hypoxic tumors.